(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
The reaction of p-cresol with benzyl alcohol in the presence of perchloric acid produces only 2-benzyl-4-methylphenol in high yield. A mathematical model has been developed for the process by Yates pattern experimental design. Bangladesh J. Sci. Ind. Res. 42(2), 187-194, 2007